The Effect Of Leadership Style On The Performance Of The West Jakarta Fire Services - Febrian, Wenny Desty; Zulhaida, Zulhaida; Ilosa, Abdiana (Lembaga Penerbitan Universitas Esa Unggul, 2021)
This study entitled The Effect of Leadership Style on Employee Performance at the West Jakarta Fire Service, which is located at Jalan Tanjung Duren Raya No. 1, RT.12/RW.2, Tanjung Duren Utara, Grogol Petamburan, RT.12/RW.2, Tj. Duren Utara, Kec. Grogol petamburan, West Jakarta City, Jakarta Special Capital Region 11470. This research will take place from June-December 2020. Population and sample in this study were all operational members of the Fire Department, totaling 134 people. The sampling method was purposive random sampling, and the number of samples was 57 people. Furthermore, the data is processed by quantitative methods using the SEM PLS 3 tool. The criteria for testing discriminant validity are based on the value of the test variable which is greater than the value of the other variables. Based on the test results in the year that the value of the x1 variable is smaller than the two y variables. Thus the test results are not discriminantly valid. The result of this study is that the value of Cronbach's alpha is more than 0.7, so it can be said that the variable is said to be reliable. The composite reliability value from the test results shows a value above 0.7, so it can be said that the data is valid. The conclusion from the test results can be said that the data is valid and reliable. Closer to 1, the better. From the test results, it is known that the NFI value is 0.68 which means the model is quite good and appropriate. Based on the test results, it is known that the Y1 variable has an R-Square value at Y of 0.781. This means that the variable X can explain the effect of the variable Y by 78.1% while the remaining 21.9% is explained by other variables outside of this study. Based on the test results, it is known that the P-value of the test results between the variables x to Y is 0.000. Based on these results, it can be concluded that the variable x has an effect on y1 and the variable x has an effect on y2. Results of the regression test show that the value of the original sample X against Y is 0.884. means that if the value of the variable x increases by 1 unit, it will increase the value of Y by 0.884.